Pollutant Emissions from Improved Cookstoves of the Type Used in Sub-Saharan Africa. Issue 8 (2nd August 2020) - Mitchell, E.J.S; Ting, Y.; Allan, J.; Lea-Langton, A.R.; Spracklen, D.V.; McFiggans, G.; Coe, H.; Routledge, M.N.; Williams, A.; Jones, J M.
ABSTRACT: Emissions from traditional cookstoves are a major health concern in developing world households. Improved cookstoves can reduce fuel use and pollutant emissions and here we compare three types of improved cookstoves widely used in Sub-Saharan Africa. These are a raised-bed charcoal stove, a rocket-type stove using wood and straw, and a gasifier stove. Laboratory measurements were made of the main gaseous pollutants, particle size distribution and composition. The genotoxicity of the particles was assessed using a comet assay. The rocket-type stove using dry wood had the highest emission factors for particulate matter and NOX . Emissions of CO and CH4 were a factor of 6–7 higher from the charcoal stove compared with the other stoves tested in this work, and also higher for burning high moisture wood. Fuel properties were critical for emitted particle size, and for the emissions of NOX, black carbon and organic matter.